Corncob-shaped ZnFe2O4/C nanostructures for improved anode rate and cycle performance in lithium-ion batteries. Issue 40 (7th May 2015) - Mao, Junwei; Hou, Xianhua; Wang, Xinyu; He, Guannan; Shao, Zongping; Hu, Shejun
<x xml:space="preserve">Abstract</x> The as-prepared corncob-shaped ZnFe2O4/C composite materials serve as anodes in lithium ion batteries and display high rate capability and enhanced recycling durability in comparison with pure ZnFe2O4 materials.